Vernakalant - Dobrev, Dobromir; Hamad, Bashar; Kirkpatrick, Peter (Nature reviews. Drug discovery, 2010)
In September 2010, vernakalant (Brinavess; Cardiome/Merck) was granted marketing authorization by the European Commission for the rapid conversion of recent-onset atrial fibrillation to sinus rhythm.
Gesehen am 08.05.2023